A Preliminary Comparison of Beef Carcases Stunned using DTS: Diathermic Syncope® or Captive Bolt in Terms of Selected Meat Quality Attributes and Plasma Biomarker Concentrations - Small, Alison; Hughes, Joanne (Animal Review, 2022)
A novel technology for inducing unconsciousness prior to slaughter has been developed (DTS). For commercial reasons meat quality attributes are important, and impacts on endocrine responses provide an indication of animal welfare. We compared endocrine, ultimate pH and meat quality (after 1 and 10 weeks of storage) attributes of cattle carcases processed using DTS with those processed using penetrative captive bolt (CB). There were no significant differences between treatments in the change in plasma cortisol, adrenocorticotropic hormone, β-endorphin and catecholamines between baseline and immediately post-slaughter, and no significant differences in terms of pH at 24 h post slaughter. There were no significant differences in pH, shear force, TBARS or drip loss between DTS and CB samples of round and loin at week 1 and week 10 post slaughter; DTS meat was yellower at quartering (MINOLTA b* P < 0.05). At week 1, DTS loins were redder (MINOLTA a*, P < 0.05) and yellower (MINOLTA b*, P < 0.05), while DTS rounds were lighter (MINOLTA L*, P < 0.05), than CB. At week 10, there were no significant meat color differences between treatments. Processing cattle using DTS results in endocrine changes and meat quality attributes that are comparable to CB.